Tourism eco-efficiency of Chinese coastal cities – Analysis based on the DEA-Tobit model. (1st November 2017) - Liu, Jia; Zhang, Junfei; Fu, Zhengben
Abstract: Tourism eco-efficiency plays an important role in the environment due to serious environment pollution and resource consumption. An evaluation of the tourism eco-efficiency of 53 Chinese coastal cities was conducted for 2003–2013, exploring the overall efficiency levels, regional differences, eco-efficiency types and influencing factors. To achieve the objectives of the study, a data envelopment analysis (DEA)-Tobit model is applied. The major findings indicate that the overall tourism eco-efficiency of Chinese coastal cities is 0.860, which means that only a few cities are effectively efficient and that most cities still have room for improvement. This finding implies that tourism development has a more negative impact on the environment and that there are substantial regional differences in efficiency. The results also show that economic and ecological indicators have significantly positive influences on the tourism eco-efficiency of Chinese coastal cities, while the number of tourists and the use of three major pollutants in the tourism industry have a negative impact. We identify several influencing factors and propose several suggestions for increasing tourism eco-efficiency and the development quality of Chinese coastal cities. Highlights: A DEA-Tobit model is applied to measure Chinese coastal tourism eco-efficiency values and its influencing factors. The overall level of China coastal tourism eco-efficiency is not high. There are obvious differences between regional coastal tourism eco-efficiency. Four types of coastal areas can be classified per efficiency values. Several factors having positive and negative impacts on tourism eco-efficiency are also discussed.